2006
DOI: 10.1152/ajplung.00079.2006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of T cell subsets to the pathophysiology ofPneumocystis-related immunorestitution disease

Abstract: .-Immune-mediated lung injury is an important component of Pneumocystis pneumonia (PcP)-related immunorestitution disease (IRD). However, the individual contribution of CD4 ϩ and CD8 ϩ T cells to the pathophysiology of IRD remains undetermined. Therefore, IRD was modeled in severe combined immunodeficient mice, and specific T cell depletion was used to determine how T cell subsets interact to affect the nature and severity of disease. CD4 ϩ cells were more abundant than CD8 ϩ cells during the acute stage of IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…5). Data from previous reports by Swain et al and Bhagwat et al are consistent with our observation of exacerbated CD4 ϩ T cell-mediated IRIS when CD8 ϩ T cells are absent during recovery of host immune function (16,27). Although CD8 ϩ T cells have long been regarded as cytotoxic cells, the CD8 ϩ T cells recruited to the lung during IRIS appear to play a more regulatory role by limiting the CD4 ϩ T cell response to Pneumocystis infection (34,35).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…5). Data from previous reports by Swain et al and Bhagwat et al are consistent with our observation of exacerbated CD4 ϩ T cell-mediated IRIS when CD8 ϩ T cells are absent during recovery of host immune function (16,27). Although CD8 ϩ T cells have long been regarded as cytotoxic cells, the CD8 ϩ T cells recruited to the lung during IRIS appear to play a more regulatory role by limiting the CD4 ϩ T cell response to Pneumocystis infection (34,35).…”
Section: Discussionsupporting
confidence: 91%
“…The mouse model of PcP-related IRIS was used, as described previously (18,27). RAG2 Ϫ/Ϫ , RAG2/IL-4R␣ Ϫ/Ϫ , and RAG2/IFN-␥R Ϫ/Ϫ mice were intratracheally inoculated with 5 ϫ 10 5 purified Pneumocystis organisms based on cyst counts.…”
Section: Micementioning
confidence: 99%
See 2 more Smart Citations
“…The immune reconstituted SCID mouse model of PCP is similar to the IRIS presentation of PCP in human patients, and provides a model for elucidating mechanisms of PCP-related IRIS. Recent discoveries using this model have determined that CD4 þ T cells are critical for mediating immunopathogenesis, whereas CD8 þ T cells serve a regulatory function by limiting the CD4 þ T-cell response (Bhagwat et al 2006;Swain et al 2006). Pharmacological manipulation of the organism in vivo found that the cyst form of Pneumocystis, which contains proinflammatory cell wall components, drives immunopathogenesis during IRIS (Linke et al 2013).…”
Section: Pathogenesismentioning
confidence: 99%